Increasing Creativity Through Fun Cooking Activities in Early Childhood at RA Al-Hikmah Jambi City - Annisa, Maulidya Venus Annisa; Tumewa Pangaribuan; Masyunita Siregar (UIN Mataram, 2024)
This research is based on the background that children's creativity in RA Al-Hikmah, Jambi City is still not well developed. This means that children cannot express their opinions and children cannot do coloring or drawing activities, children cannot produce various innovative ideas and children cannot create their own work. This research aims to determine children's creativity before and after being given action using fun cooking activities and to find out whether fun cooking activities can increase children's creativity. This research is a type of Classroom Action Research. The research subjects were children aged 5-6 years in group B2 at RA Al-Hikmah, Jambi City with a total of 25 children. Data collection techniques use observation. The data analysis technique is by comparing the total creativity value with the maximum value then multiplying by 100% or using a percentage correction formula. The results of the research prove that the increase in children's creativity through fun cooking activities in cycle I increased from 31.71% to 45.28%. Furthermore, in cycle II there was an increase from 52.42% to 71.29%. Cycle III experienced an increase from 78.28% to 84.71%. The conclusion of this research is that fun cooking activities can increase the creativity of young children at RA Al-Hikmah Jambi City in the BSB category or high category, namely 84.71%.